Antioxidant Molecules as a Source of Mitigation of Antibiotic Resistance Gene Dissemination - Ortiz de la Rosa, José Manuel (Antimicrob Agents Chemother, 2021)
Escherichia coli is the most commonly identified human pathogen and a prominent microorganism of the gut microbiota. Acquired resistance to antibiotics in this species is driven mainly by horizontal gene transfer and plasmid acquisition. Currently, the main concern is the acquisition of extended-spectrum β-lactamases of the CTX-M type in E. coli, a worldwide-observed phenomenon. Plasmids encoding CTX-M enzymes have different scaffolds and conjugate at different frequencies. Here, we show that the conjugation rates of several plasmid types encoding broad-spectrum β-lactamases are increased when the E. coli donor strain is exposed to subinhibitory concentrations of diverse orally given antibiotics, including fluoroquinolones, such as ciprofloxacin and levofloxacin, but also trimethoprim and nitrofurantoin. This study provides insights into underlying mechanisms leading to increased plasmid conjugation frequency in relation to DNA synthesis inhibitor-type antibiotics, involving reactive oxygen species (ROS) production and probably increased expression of genes involved in the SOS response. Furthermore, we show that some antioxidant molecules currently approved for unrelated clinical uses, such as edaravone, p-coumaric acid, and N-acetylcysteine, may antagonize the ability of antibiotics to increase plasmid conjugation rates. These results suggest that several antioxidative molecules might be used in combination with these “inducer” antibiotics to mitigate the unwanted increased resistance plasmid dissemination.